PUBLIC ART SPACE IN BANJARBARU - Permatasari, Laila Noor; Andini, Dila Nadya (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Banjarbaru has the opportunity to develop local potential in the field of art, especially works of fine art in line with the era of globalization so that there needs to be a container of interest as well as interactive public education facilities that can generate curiosity and mindfulness to provide new experiences in the meaning of art for the general public. Therefore, the Public Art Space in Banjarbaru is designed as a solution to the architectural problems raised to meet these needs. The design of Public Art Space in Banjarbaru applies the concept of mindfulness which refers to 3 design elements namely sequential, lighting, and pause then completed by the approach of Expressionist Architecture through the processing of architecture elements, namely the shape of space and the form of circulation. The design idea aims to realize a functional design for its users while making the Public Art Space in Banjarbaru an expressive unit in implementing the process of meaning art related to the value of fine art from local artists both individually and collectively presented to the general public.